1989
DOI: 10.1080/09593338909384778
|View full text |Cite
|
Sign up to set email alerts
|

Air quality in passenger cabins of DC‐9 and MD‐80 aircraft

Abstract: The air quality in the passenger cabins of DC-9 and MD-80 aircraft has been studied on 48 representative flights. A portable air sampling case was used. No observations of health effects were made. The average levels of the components related to environmental tobacco smoke, were for respirable suspended particles 60, 250, 160 and 220 g/m 3 ; for nicotine 5, 41, 21 and 32 g/m 3 ; and for carbon monoxide 0.6, 1.1, 0.8 and 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…The optimal relative humidity for comfort is about 40 to 70 % (Rayman 1997), and the American Society of Heating, Refrigeration, and Conditioning Engineering standard for buildings (ASHRAE 1999) is for a minimum relative humidity of 20 %. The bleed air from the engines of a modern jet, which is used to maintain cabin pressure, has a relative humidity of 0.5 to 1 % (Space et al 2000;Spengler and Wilson 2003), and most of the moisture within the cabin is provided by the passengers (Malmfors et al 1989;O'Donnell et al 1991), although there is also some moisture from galleys and toilets (O'Donnell et al 1991). At cruise altitudes, the cabin humidity depends on passenger load (Malmfors et al 1989;Arnold et al 2000) and is typically 5 to 20 %, but can be as low as 2 % (Backman and Haghighat 2000;Wieslander et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal relative humidity for comfort is about 40 to 70 % (Rayman 1997), and the American Society of Heating, Refrigeration, and Conditioning Engineering standard for buildings (ASHRAE 1999) is for a minimum relative humidity of 20 %. The bleed air from the engines of a modern jet, which is used to maintain cabin pressure, has a relative humidity of 0.5 to 1 % (Space et al 2000;Spengler and Wilson 2003), and most of the moisture within the cabin is provided by the passengers (Malmfors et al 1989;O'Donnell et al 1991), although there is also some moisture from galleys and toilets (O'Donnell et al 1991). At cruise altitudes, the cabin humidity depends on passenger load (Malmfors et al 1989;Arnold et al 2000) and is typically 5 to 20 %, but can be as low as 2 % (Backman and Haghighat 2000;Wieslander et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The bleed air from the engines of a modern jet, which is used to maintain cabin pressure, has a relative humidity of 0.5 to 1 % (Space et al 2000;Spengler and Wilson 2003), and most of the moisture within the cabin is provided by the passengers (Malmfors et al 1989;O'Donnell et al 1991), although there is also some moisture from galleys and toilets (O'Donnell et al 1991). At cruise altitudes, the cabin humidity depends on passenger load (Malmfors et al 1989;Arnold et al 2000) and is typically 5 to 20 %, but can be as low as 2 % (Backman and Haghighat 2000;Wieslander et al 2000). During take off and landing, the bleed air from the engines is shut off so that full power is available from the engines (Arnold et al 2000;Lindgren 2003); in these periods, 100 % of the cabin air is re-circulated, and the humidity is therefore higher than at cruise altitudes, but is still low.…”
Section: Introductionmentioning
confidence: 99%
“…A 30 May 1989 bill to CIAR from Covington & Burling contained charges for ''continued work in connection with the SAS project, including consulting with Professor Malmfors and others in Washington and Stockholm concerning their research report, consulting with the Executive Director and Company scientists concerning the draft report and related matters, and editing the draft report…''. 83 A substantial difference existed between the published IFAQ study results paper ''Air Quality in Passenger Cabins of DC-9 and MD-80 Aircraft'' 84 published under Malmfors' authorship in the journal Environmental Technology Letters in 1989, and the draft report TNO had produced. 74 While the TNO draft reported standard deviations and full ranges for recorded values (reproduced in fig 1), Malmfors et al reported standard errors of the mean and 5%/95% range in separate tables (reproduced in fig 2 and 3).…”
Section: Misleading Presentation Of Resultsmentioning
confidence: 99%
“…68 Paediatric and Perinatal Epidemiology, which published the article by Sullivan and Barlow, 16 requires that acknowledgments include "details of funding." The Sullivan review, 16 as well as the other cases described above, 15,63,64,66,67 illustrates the need for journals to require complete disclosure of all sponsor involvement in the conduct of a study and the preparation of the manuscript. However, such disclosure guidelines have been demonstrated repeatedly not to be effective with the tobacco industry, which seeks actively to minimize its role.…”
Section: Discussionmentioning
confidence: 99%
“…Those who support acceptance of tobacco industry funds argue that academic authors retain the right to publish their work and maintain final approval of the written product, 62 but this argument fails to recognize that the tobacco industry funds work to ensure that messages favorable to the industry are published and disseminated. For example, in 1988, PM led other tobacco companies in designing and controlling an airline indoor air quality study 63 that downplayed exposure to SHS and its potential health effects when smoking restrictions on airlines were being debated. 64 In 1995, the industry generated and controlled the conduct and content of a study, eventually published under Peter Lee's name, 65 that was designed specifically to refute a landmark study on lung cancer and SHS among nonsmoking women.…”
Section: Discussionmentioning
confidence: 99%